Multisystem inflammatory syndrome in the context of paediatric COVID‐19 infection in the Republic of Ireland April 2020 to April 2021. (6th September 2022) - Treston, Bryony; Petty‐Saphon, Naomi; Collins, Abigail; Murray, Sarah; Colgan, Aoife; Fitzgerald, Eoin; Hassan, Mahmoud; Forde, Karina; O'Farrell, Anne; Sayers, Gerardine; Linnane, Niall; Franklin, Orla; et al.
Abstract: Aim: Our aim was to describe the epidemiology of multisystem inflammatory syndrome in children (MIS‐C) in the Republic of Ireland, in the context of all cases of COVID‐19 in children, during the first year of the SARS‐CoV‐2 pandemic. Methods: Cases of MIS‐C were identified by prospective surveillance in Irish hospitals from April 2020 to April 2021. Paediatric COVID‐19 cases and outbreaks in schools or childcare facilities were notified to and routinely investigated by Public Health. Univariate and bivariate analyses were carried out in Excel, Stata and JMP statistical package. Results: Fifty‐four MIS‐C cases (median age 7.58 years; males 57%) were identified over the study period. MIS‐C incidence was higher in certain ethnicities ('black' 21.3/100, 000 [95% CI 4.3–38.4]; and 'Irish Traveller' 14.7/100, 000 [95% CI −5.7‐35.1]) than those of 'white' ethnicity (3.4 /100, 000). MIS‐C cases occurred in three temporal clusters, which followed three distinct waves of community COVID‐19 infection, irrespective of school closures. Formal contact tracing identified an epidemiological link with a COVID‐19‐infected family member in the majority of MIS‐C cases (77%). In contrast, investigation of COVID‐19 school outbreaks demonstrated no epidemiological link with MIS‐C cases during the study period. Conclusion: Efforts at controlling SARS‐CoV‐2 transmission in the community may be a more effective means to reduce MIS‐C incidence than school closures. Establishing a mandatory reporting structure for MIS‐C will help delineate the role of risk factors such as ethnicity and obesity and the effect of vaccination on MIS‐C incidence.